OIL OF PANDAN KELAPA HUTAN (Pandanus jiulianettii Martelli): PHYSICOCHEMICAL PROPERTIES, TOTAL PHENOLS, TOTAL CAROTENE, VITAMIN E AND ANTIOXIDANT ACTIVITY - ZEBUA, LISYE IRIANA; PURNAMASARI, VITA (Jurnal Biologi Udayana; Vol 21 No 2 (2017): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2017.vol21.i02.p05, 2018)
Pandanus plant is one of the important plant in Papua and Papua New Guinea. Traditionally pandanus plant is used by local people for lots of daily activities and daily needs, start from food flavoring, medicine, to religious ceremony needs. Pandan kelapa hutan fruits (P. jiulianettii Martelli.) is one of a kind of pandanus that been used from generation to generation the highlands of Papua and Papua New Guinea for the food ingredients. This research aims to determine the physicochemical properties, total phenol, total carotene, vitamin E and antioxidant activities of the forest coconut pandan oil (P. jiulianettii Martelli.) extracted using an aluminum pan. Physicochemical character that been analyzed is specific gravity, iod value, saponification value, free fatty acid content, acid value and peroxide value. Total phenol, total carotene and vitamin E measured respectively using Folin-Ciocalteu method, spectrophotometry method and colorimetric methods. Antioxidant activities is measured using a method that called DPPH. The result shows the pandan coconut oil has 1,00059 of specific gravity, 65.87 g/100gr of iod, 201,28 mg/g of saponification, 4.26% of acid and 5.64 Meq/kg of peroxide. The content of total phenols, total carotene and vitamin E respectively are 48.55 ppm, 2.75 µg/g and 5.0303 mg/100g. The antioxidant IC50 measuring result shows the value is 45.83 mg/mL.